Comparison of Telephone and Televideo Modes for Delivery of Genetic Counseling: a Randomized Trial. Issue 2 (15th December 2017) - Voils, Corrine I.; Venne, Vickie L.; Weidenbacher, Hollis; Sperber, Nina; Datta, Santanu
Abstract: Telephone and televideo have yielded equivalent patient satisfaction and psychosocial outcomes when compared to in‐person genetic counseling, yet little is known about how they compare to one another. In this randomized controlled trial, veterans received genetic counseling via telephone or traveled to a clinic to participate via encrypted televideo. Knowledge and visit satisfaction were assessed 2 weeks later. Travel time, mileage, and out‐of‐pocket costs were calculated for videoconferencing. Qualitative interviews were conducted with patients and counselors to assess acceptability. Of the 20 male patients randomized to telephone, 90% received counseling and provided outcomes; of the 18 randomized to televideo, 67% received counseling and 50% provided outcomes. Telephone patients answered a mean of 4.4 of eight questions correctly at baseline and 4.7 at follow‐up; televideo means were 5.6 and 6.5, respectively. Satisfaction was 25.2 out of 30 for telephone and 26.9 for televideo. Televideo patients incurred a median of 2.8 h of travel time, 40 roundtrip miles, and 67.29 in costs. Patients and counselors found both modes acceptable for providing education and answering questions. Although patients liked the flexibility of telephone, counselors felt patients missed more appointments and were distracted when using telephone. A noted advantage of videoconferencing was reading body language. Further evaluation of alternative delivery modes is needed.